1、带括号的加法用减法 12+( )=16 15+( )=20 ( )+3=12 3+( )=20 16+( )=19 ( )+12=18 3+( )=16 5+( )=14 8+( )=13 ( )+4=16 8+( )=16 8+( )=16 ( )+11=14 ( )+6=13 ( )+14=18 9+( )=17 7+( )=11 ( )-8=9 ( )-8=3 ( )-14=3 带括号的加法用减法 ( )-8=8 ( )-11=6 ( )-6=13 ( )-9=3 ( )-6=7 ( )-5=7 ( )-7=16 ( )-9=9 6+( )=11 7+( )=11 5+( )=14 3+
2、( )=16 2+( )=17 15+( )=20 12+( )=16 11+( )=14 9+( )=17 8+( )=16 8+( )=13 16+( )=19 带括号的加法用减法3+( )=20 8+( )=15 6+( )=13 9+( )=12 ( )-8=9 12+( )=16 6+8=( ) ( )-5=7 15+( )=20 19-( )=12 ( )+3=12 6+( )=11 ( )-6=13 11+( )=14 3+( )=20 ( )-8=3 2+( )=17 13-( )=6 6+8=( ) ( )+13=13带括号的加法用减法11-( )=9 7+( )=14 16
3、+( )=19 ( )-14=3 3+( )=16 15-9=( ) ( )+12=18 16-7=( )5+( )=14 ( )-6=7 8+( )=13 18-( )=6( )+4=16 5+13=( ) 12+8=( ) ( )-8=8 14-( )=9 ( )+6=13 11-( )=3 8+( )=16带括号的加法用减法7+( )=11 ( )+11=14 ( )-7=16 19-7=( ) ( )+5 = 18 ( )+14=18 9+5=( ) ( )-11=6 ( )-9=3 9+( )=17 8+( )=16 ( )712 ( )817 ( )211 ( )614 ( )71
4、1 ( )312 ( )5 12 ( )712 13+( )=18 带括号的加法用减法9( )=11 8( )=12 7( )=12 6( )= 125( )=11 15( )=6 14( )=6 12( )=511( )=5 13( )=8 9( )=13 ( )+5=11 ( )+9= 13 ( )+7=12 ( )+7=14 ( )+4=12( )712 ( )817 ( )211 ( )614带括号的加法用减法( )711 ( )312 ( )5 12 ( )712 13+( )=18 9( )=11 8( )=12 7( )=12 6( )= 12 5( )=11 15( )=6 1
5、4( )=6 12( )=5 11( )=5 13( )=8 9( )=13( )+5=11 ( )+9= 13 ( )+7=12 ( )+7=14 带括号的加法用减法( )+4=12 ( )712 ( )817 ( )211 ( )614 ( )711 ( )312 ( )5 12 ( )712 13+( )=18 9( )=11 8( )=127( )=12 6( )= 12 5( )=11 15( )=6( )712 ( )817 ( )211 ( )614带括号的加法用减法( )711 ( )312 ( )5 12 ( )71213+( )=18 9( )=11 8( )=12 7(
6、)=12 6( )= 12 5( )=11 15( )=6 14( )=6 12( )=5 11( )=5 13( )=8 9( )=13( )+5=11 ( )+9= 13 ( )+7=12 ( )+7=14 带括号的加法用减法( )+4=12 14( )=6 12( )=5 11( )=5 13( )=8 9( )=13 ( )+5=11 ( )+9= 13 ( )+7=12 ( )+7=14 ( )+4=12 ( )712 ( )817 ( )211 ( )614 ( )711 ( )312 ( )5 12 ( )712 13+( )=18带括号的加法用减法9( ) =11 8( )=1
7、2 7( )=12 6( )= 125( )=11 15( )=6 14( )=6 12( )=5 11( )=5 13( )=8 9( )=13 ( )+5=11( )+9= 13 ( )+7=12 ( )+7=14 ( )+4=12( )712 ( )817 ( )614 ( )711 带括号的加法用减法( )312 ( )5 12 ( )712 13+( )=189( )=11 8( )=12 7( )=12 6( )= 125( )=11 15( )=6 14( )=6 12( )=511( ) =5 13( )=8 9( )=13 ( )+5=11( )+9= 13 ( )+7=12 ( )+7=14 ( )+4=12